ANALISIS KELAYAKAN BISNIS KONVEKSI DITINJAU DARI ASPEK PASAR DAN PEMASARAN (STUDI PADA KONVEKSI DEZAINLA DI KOTA BANDAR LAMPUNG) - Bani Nurul Adha; Hartono Hartono; Fenny Saptiani (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine and analyze the feasibility of the Bandar Lampung Convection Dezainla business through its market and marketing aspects. This type of research is descriptive research using a qualitative approach. Data collection techniques are observation, interviews and documentation. The results of the research show that from the market aspect, it has good market potential and market share, marked by sales growth in 2021-2022, increasing by 74.9%. In the marketing aspect the products produced are of good quality, prices that can compete with other competitors, the distribution channels used have utilized sales through resellers, and implemented promotions using a multi-channel marketing strategy by utilizing various available social media platforms such as Instagram, Youtube , Website, Facebook, Tiktok, and WhatsApp. Thus, from the market and marketing aspects that have been studied by researchers, the Dezainla convection is already good so that the Dezainla convection can be declared feasible to run from the market and marketing aspects.